Perancangan Sistem Informasi Penjualan Web untuk Efisiensi Administrasi UMKM Makanan dan Minuman - Fadhil Ezar Rahman; Binastya Anggara Sekti (Ikatan Ahli Informatika Indonesia, 2025)
This research focuses on the design of a web-based sales information system aimed at assisting micro, small, and medium enterprises (MSMEs), particularly in the food and beverage sector, in managing their sales activities more effectively. The utilization of information technology is expected to improve operational efficiency and support the digitalization process, which is essential for business growth and sustainability. The proposed system includes key features such as an activity dashboard, modules for managing sales and purchase transactions, user account management, and product stock monitoring. The development method applied in this research is the Software Development Life Cycle (SDLC) using the Waterfall model, which consists of several stages: requirement analysis, system design, implementation, and testing. The results demonstrate that the system is capable of automating administrative processes that were previously managed manually. This leads to significant improvements in accuracy, speed, and accessibility of sales and purchase data With the implementation of this information system, MSMEs can manage transactions in a more structured manner, minimize recording errors, and support better business decision-making based on available data. This research is expected to provide a solution for MSMEs in adapting to digital transformation while contributing to the acceleration of digitalization in the food and beverage sector